2022
DOI: 10.1002/aur.2774
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance, praxis, and social skills in autism spectrum disorder and developmental coordination disorder

Abstract: Previous research has shown that individuals with autism spectrum disorder (ASD) and developmental coordination disorder (DCD) may have overlapping social and motor skill impairments. This study compares ASD, DCD, and typically developing (TD) youth on a range of social, praxis and motor skills, and investigates the relationship between these skills in each group. Data were collected on participants aged 8–17 (n = 33 ASD, n = 28 DCD, n = 35 TD). Overall, the clinical groups showed some similar patterns of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 96 publications
0
19
0
3
Order By: Relevance
“…Our behavioral results indicate that 80% of the ASD group have motor impairments as measured by the MABC-2, which are consistent with prior data on motor impairment in ASD 38 40 . Please refer to recent papers by our group in largely the same sample, which discuss in detail the behavioral differences between these two groups 18 , 41 . Here, we aimed to find the presence of specific white matter diffusivity differences in ASD that do not overlap with other developmental motor deficits, namely DCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our behavioral results indicate that 80% of the ASD group have motor impairments as measured by the MABC-2, which are consistent with prior data on motor impairment in ASD 38 40 . Please refer to recent papers by our group in largely the same sample, which discuss in detail the behavioral differences between these two groups 18 , 41 . Here, we aimed to find the presence of specific white matter diffusivity differences in ASD that do not overlap with other developmental motor deficits, namely DCD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies suggest that individuals with ASD have substantial overlap in motor impairments with DCD, and qualify for DCD on gold standard DCD assessments, such as the Movement Behavioral Assessment for Children (MABC 12 19 ; see for a systematic review 20 ). Nevertheless, ASD and DCD groups may significantly differ on more social motor tasks, such as imitation (ASD with significantly poorer imitation) 18 . Further, white matter studies on DCD groups have also found diffusivity differences in several motor tracts previously implicated in ASD, including the descending tracts, cerebellar tracts, and the splenium of the corpus callosum 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that DCD affects 5–6% of children and may significantly interfere with activities of daily living and school performance [ 21 , 23 ]. DCD is also a common comorbidity in children with ASD, with approximately 60–90% meeting the criteria for DCD [ 24 , 25 , 26 ]. However, 90% of children identified with DCD do not have a co-occurring diagnosis of ASD [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…While in ASD, social impairment is a key diagnostic criterion, recent studies indicate that children with DCD also commonly have social deficits including social anxiety, less peer support, and poor social communication [ 21 , 53 ]. In fact, our prior work showed that about 36% of children with DCD fell into the clinical range of social deficits on the SRS-2 [ 25 ]. Although these social issues are often described as secondary symptomologies, derived from having less social peer interactions by not participating in social activities that require motor skills such as sports teams, instrumental groups, or art classes [ 54 , 55 ], an alternative interpretation is that some social symptoms may be primary in DCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation